Act of Jan. 31, 1888, § 1 Wash. Territory Sess. Laws 100, 100-101 (Thomas H. Cavanaugh 1888). - (:unkn) unknown (My University, 1888)
Every person who shall in a reckless, careless or negligent manner discharge, in the vicinity of an inhabitated dwelling house, or in the streets of an incorporated city, or unincorporated town, any firearm, shall be deemed guilty of a misdemeanor, and, upon conviction thereof, shall be punished by fine not exceeding one hundred dollars, or by imprisonment in the county jail not exceeding thirty days, or both such fine and imprisonment.
Keywords: DISCHARGE